Penerapan Prinsip Seni Rupa Pada Gambar Buah dan Keranjang Karya Peserta Didik SMA Negeri 1 Hamparan Perak - Iman Priadi; Mesra Amirudin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the work of students in drawing shapes based on the principles of fine art. The objects drawn are fruit and fruit baskets. The population of this study were all students of class X with a total of 324 students, and the sample was 36 students' work. This study used descriptive qualitative method. The results of this study indicate that the overall work produced by applying the principles of fine arts has a fairly good score with an average score of = 81.86 in the category C (good enough) on the principle of unity. Then in the principle of composition an average value of = 80.35 in the category C value (good enough), then on the principle of perspective, the average value = 81.67 in the category C value (good enough) and the principle of dark-light fine acquisition value = 82.15 in the category of value (good enough). So from that the overall acquisition of an average value = 81.51 in the category C value (good enough).